BIOLEACHING OF NICKEL FROM GAG ISLAND LIMONITIC ORE BY THE ASSISTANCE OF MIXOTROPIC BACTERIA - ERYO PRATAMA , BETRI
Bioleaching is a leaching of metals from ore by the assistance of microbe activities such as bacteria and fungis. Research works that have been done on the area of bioleaching are mostly developed for sulfide mineral and focused on the Research of heterotroph bacteria which consumes organic substances for their life and chemolitotroph which requires the presence of iron and sulfur for their life. In this research, the extraction of nickel from laterite ore of limonitic type from Gag Island by using mixotropic bacteria (i.e. those which can benefit either organic substance and chemical substance for their life) was studied. The mixotropic bacteria used are Alicyclobacillus ferrooxidans, Bacillus mucilaginosus and Pseudomonas putida species which have been isolated from a mining area in Sorowako, South Sulawesi province. The research activities consisted of preparation of the ore sample, bacteria culturing in Fe-broth media, leaching in rotating shaker flask under shaking speed of 180 rpm and measurements of dissolved Ni, Fe, Mg as well as the alteration of solution pH for 28 day of leachings. Series of bioleaching experimental works have been carried out to study the effects of the tyoe of organic carbon sources (i.e. molasse and leachate), additions of sulphur elemental, the distribution of ore particle size, the innoculum percentage and the solid percentage on the nickel extraction percentage and the pH alteration by time. As a matter of comparison, the leaching tests by using commercial organic acid which is predicted to be generated by mixotropic bacteria (i.e. citric acid) were also conducted. The investigation results show that the highest nickel extraction of 34.3% was obtained from the bioleaching test with the ore particle distribution of -60 + 80 mesh, using leachate as substrate for organic carbon source, under 20% w/w addition of elemental sulphur after 28 day of leaching. Under this condition, dissolved iron and magnesium are only 1.15% and 6.8%, respectively indicated a good selectivity of the bioleaching to iron and magnesium. The extraction level of nickel seems to be improveable since the solution pH still tends to decrease after 28 day of leaching. Sulphate analysis detected the formation of sulphuric acid on the leach solution. The further addition of sulphur to 30% w/w reduces the extraction percentage of Ni, predicted due to parts of undissolved sulphur which hinders the contact of leaching reagent with the ore surface. The reduce of ore particle size distribution from -60 + 80 mesh to -100 + 200 mesh and -200 mesh tends to decrease the extractio percentage of nickel. Leaching test with citric acid commercial in rotating shaker for 28 day resulted in the highest nickel extraction percentage of 26.14%, obtained from the leaching with 1M citric acid and ore particle size of 60 + 80 mesh, which is lower than that of bioleaching.